Costing the intergovernmental negotiating body (INB) process. - Clare Wenham; Akhila Potluru (PLOS Global Public Health)
The Intergovernmental Negotiating Body (INB) was established to draft and negotiate a pandemic instrument to strengthen pandemic preparedness and response (PPR). This has been carried out under the auspices of the World Health Organization (WHO), and has to date involved 15 sessions in Geneva, plus countless hours both in informal working groups, and in capitals working on government positions on each substantive issue. This all comes at a cost, both in terms of human resource and travel costs associated with the development of an international treaty and its associated process. We begin to quantify the cost of this process as approximately US$ 201,343,032. If we also consider estimated costs for the parallel WGIHR process to be US$56,024,830, we estimate the total cost of this combined governance development to be US$257,367,862. We position this in the context of how much pandemic preparedness is thought to cost on an annual basis, and the opportunity costs of investing in this governance process instead of more operational areas of health security. Moreover, in doing so, we offer one of the first financial estimates of the cost of developing and negotiating multilateral treaties.